(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
This study aims to determine the feasibility of administratively implementing a deconcentrated and process-based institutional management model at the University of Guayaquil, as well as the proposal of a management model that allows the execution of strategic, business and support processes at the University of Guayaquil, in order to achieve a significant institutional transformation. For this purpose, a survey and analysis of the current process management at the UG was carried out, which allows proposing to the authorities the tools and mechanisms through which the implementation of processes could be made more viable and thus comply with the Plan of Excellence proposed by the Intervention Commission, which will lead the institution to overcome the D category in which it is currently located.